PENAKSIR RASIO REGRESI LINEAR UNTUK RATA-RATA POPULASI MENGGUNAKAN VARIABEL TAMBAHAN, KOEFISIEN VARIASI DAN KOEFISIEN KURTOSIS - Malini Anggraeni; Sigit Sugiarto; Rustam Efendi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This paper discusses three ratio  regression linear  estimators for population mean Y using two auxiliary variables X and , Z using the coefficient of variation and coefficient of kurtosis on simple random sampling.  This paper is a review of  the article Singh  et. al [Statistics in Transition  10(1): 85-100]. The three estimators are biased estimators and their  mean square errors  are  determined.  Each  estimator  compared to  the value of the mean square error.  Comparison shows that the estimator with the minimum mean square error is an efficient estimator.